(untitled) (Journal of Academic Finance, 2023)
Purpose: Many studies show that SMEs have difficulty accessing bank loans. These, in fact, would be characterized by a strong informational opacity which would lead banks to be more reluctant in their financing. The objective of this article is to analyze the signaling role of the contribution of the entrepreneur, debt, dividends, and guarantees in the limitation of information asymmetries of Malian SMEs. Methodology: To achieve our objective, we used chi-square correlation tests as well as the logistic regression method on a sample of 217 Malian SMEs. Results: The results of these tests show that the financial signals relating to the contribution of the entrepreneur and to the dividends are the most relevant in reducing the asymmetries of information of the SMEs surveyed. These results then suggest an improvement in the Bank-SME financing relationship in the presence of these financial signals. Originality: This article aims to empirically verify the ability of certain signals, widely discussed in the theoretical literature, to reduce the existing information asymmetries between banks and companies in the credit market. Moreover, the study of the relationship signals and information asymmetry is very rare in the context of the Bank-SME financing relationship in Mali.